How “alternative” alternative urban policies really are? - Wojciech Kębłowski; Mathieu Van Criekingen (Métropoles)
In recent years, participatory budgeting has been often regarded as an example of an alternative urban policy experience, detached from the entrepreneurial mainstream. Despite its increasing popularity amongst urban policy analysts, activists and practitioners, however, few works have effectively assessed the actual “alternative” character of policy practices carrying the participatory budgeting label in different urban contexts. This paper engages in such a critical assessment. We first build an analytical framework theoretically informed by Lefebvre’s conceptualisation of the “right to the city” as well as by elements put forward in the critical literature on citizens’ participation in urban policy-making. We then apply this framework to examine participatory budgeting practices in two different urban contexts, namely Cordoba in Southern Spain and Sopot in Northern Poland. Our findings suggest that the capacity of participatory budgeting to constitute an alternative to urban entrepreneurialism is conditioned by a number of intricate aspects. Although the model travels intensively around the globe as a benchmark for “alternative” policy, the actual practices of participatory budgeting may follow aims and produce results that are in fact to a large extent in tune with urban entrepreneurialism.